Runoff Coefficient Analysis After Regional Development in Tambakbayan Watershed, Yogyakarta, Indonesia - Slamet Suprayogi; M Widyastuti; M Pramono Hadi; Nugroho Christanto; Tommy Andryan Tivianton; Gita Oktaviani Fadhilah; Laelina Rahmawati; Lintang Nur Fadlillah (Jurnal Ilmu Lingkungan, 2022)
The Tambakbayan Watershed has experienced changes in its land utilization. Based on land-use data from 2006 and 2017, built-up land was found to have encroached on vegetated areas and showed a substantial increase in area. Such conversion can alter and modify runoff coefficients, as a measure of watershed response. This research aimed to evaluate land-use change in the watershed from 2006 through 2017 and its effects on runoff coefficients. It used descriptive quantitative methods combining literature study and data calculation. The secondary data were obtained from digital land-use maps (RBI) in 2006 and 2017, SRTM images, soil types, and the drainage network of the watershed. Runoff coefficient analysis confirmed that the land-use change between 2006 and 2017 caused by regional development increased the runoff coefficients of the watershed observed.ABSTRAKDaerah Aliran Sungai Tambakbayan telah terjadi perubahan, berdasarkan data penggunaan lahan tahun 2006 dan tahun 2017. Perubahan yang terjadi berupa meningkatnya lahan terbangun dan berkurangnya lahan bervegetasi. Perubahan penggunaan lahan yang terjadi dapat mengakibatkan perubahan respon DAS yang dikuantifikasikan dalam bentuk koefisien aliran. Tujuan penelitian adalah mengevaluasi perubahan penggunaan lahan daerah penelitian dari tahun 2006 dan 2017, kaitannya dengan koefisien aliran. Metode yang digunakan adalah deskriptif kuantitatif berdasarkan studi pustaka dan perhitungan. Data sekunder yang digunakan adalah Peta Rupa Bumi Digital Indonesia Tahun 2006 dan 2017, Citra SRTM DAS Tambakbayan, Jenis Tanah DAS Tambakbayan, dan Jaringan Drainase DAS Tambakbayan. Perubahan penggunaan lahan akibat perkembangan wilayah, mengakibatkan peningkatan koefisien aliran pada tahun 2017 apabila dibandingkan dengan koefisien aliran pada tahun 2006.